Xanthoma in the external acoustic meatus - A. Duvekot; V. van Dis; L.L. Veder (Elsevier, 2021)
Objectives: a unique case of a xanthoma in the external ear canal of a pediatric patient is presented in this case report. We describe and resume the current literature on xanthomas in the head and neck area. Methods: clinical and intraoperative findings are reported and the presumed mechanisms for the emergence of xanthomas are discussed. We furthermore described the pathologic and immunohistochemical characteristics. Results: xanthomas are mostly seen in patients with lipid metabolism disorders or hyperlipidemia. However, they can be present in normolipemic patients and are also associated with hematologic disease. Literature on the existence of xanthomata in the head and neck area is rare and there are no case reports in the pediatric population to the best of our knowledge. Besides the clinical presentation, characteristic histopathological features can confirm the diagnosis. When features are overlapping, immunohistochemistry can be necessary. Conclusion: since different subtypes of xanthoma have specific clinical and histopathological features and are associated with typical underlying disease, in our opinion histopathologic confirmation, especially in the pediatric patient, is important. This enables accurate referral to a specialized clinician to identify and eventually treat the underlying metabolic or hematologic disease.